BK Virus–Associated Nephropathy: Current Situation in a Resource-Limited Country - P. Yooprasert (2019)
© 2017 The Authors Background: Data on BK virus–associated nephropathy (BKVAN) and treatment strategy in a resource-limited country are scarce. This study aimed to evaluate epidemiology of BKVAN and its situation in Thailand. Methods: A retrospective analysis was conducted among adult kidney transplant recipients at Ramathibodi Hospital from October 2011 to September 2016. Patients' demographic data, information on kidney transplantation, immunosuppressive therapy, cytomegalovirus and BK virus infections, and allograft outcomes were retrieved and analyzed. Results: This study included 623 kidney transplant recipients. Only 327 patients (52.49%) received BK virus infection screening, and 176 of 327 patients had allograft dysfunction as a trigger for screening. BKVAN was identified in 39 of 327 patients (11.93%). Deceased donor transplantation and cytomegalovirus infection were associated with a higher risk of BKVAN (odds ratio = 2.2, P =.024, 95% confidence intervals [1.1, 4.43], and odds ratio = 2.6, P =.006, 95% confidence intervals [1.29, 5.26], respectively). BKVAN patients were at significantly higher risk for allograft rejection (P <.001) and allograft failure (P =.036). At the end of the study, 4 graft losses were documented (12.12%). Conclusions: BKVAN was associated with high rate of allograft rejection and failure. However, surveillance of its complications has been underperformed at our facility. Implementing a formal practice guideline may improve allograft outcome in resource-limited countries.